Utilização de telas de sombreamento e mulching no cultivo de gladíolo e validação do modelo PhenoGlad no Paraná - Becker, Dislaine (2021)
The gladiolus is an important cut flower, usually cultivated in a conventional way throughout the year, however, in some times and regions, extreme temperatures can damage the flower stalks. Due to the problems related to intensive soil cultivation and the risk of damage from high temperatures, the use of natural mulching is an alternative for soil conservation and preservation, and shading screens are useful to avoid and reduce possible damage to the stems. Mathematical models that simulate crop development are important tools to help farmers with production planning. The objective of this work was to characterize the growth, development, quality of flower stalks, evaluate the anatomy and physiology of gladiolus plants using shade and mulching screens, as well as validate the PhenoGlad model for the state of Paraná and determine the date planting for sale of flowers to the Dead. Field experiments were carried out in four growing seasons: 1 (March-June); 2 (August-November); 3 (August to November) and; 4 (October December). The experimental area is located at the Federal Technological University of Parana, Campus Dois Vizinhos. The gladiolus cv. White Goddess was cultivated in beds with natural mulching and without mulching. The shading screens used were 35%, in black, silver, red and no screen (control). For validation of the PhenoGlad model, field experiments were carried out in 2019 in five municipalities in the state of Paraná (Cascavel, Dois Vizinhos, Marechal Cândido Rondon, Palotina and Santa Helena). In Dois Vizinhos, gladiolus was cultivated in beds with and without soil cover (natural mulching) and, in the other places, it was cultivated with beds without soil cover. To determine the planting date for sale on the day of the dead (November 2), 20 municipalities in the State of Paraná were selected. The model was run for each location and year of meteorological data for the early, intermediate II and late cycles. The 35% shading screens and mulching cultivation promote greater growth (number of leaves, leaf area, leaf area index and height) of gladiolus plants. The crop development stages are influenced by the season and screen, but the duration of the cycle is dependent on the air temperature factor and cultivation with mulching does not interfere with it. Gladiolus cultivation using shading screens and soil mulching showed influence on some growth and development characteristics with anatomical and physiological changes, demonstrating the phenotypic plasticity of the crop in adapting, enabling cultivation under different conditions. The use of silver and red shading screens reduced damage from extreme temperatures in times with climatic risks. Mulching is an alternative to gladiolus cultivation in soil conservation systems.